Coherent Population Trapping Resonances in Cs Atomic Vapor Layers of Micrometric Thickness - A. Krasteva; D. Slavov; S. Cartaleva (International Journal of Optics)
We report on a novel behavior of the electromagnetically induced absorption (EIA) resonance observed on the D2 line of Cs for atoms confined in cells with micrometric thickness. With the enhancement of light intensity, the EIA resonance amplitude suffers from fast reduction, and even at very low intensity (W < 1 mW/cm2), resonance sign reversal takes place and electromagnetically induced transparency (EIT) resonance is observed. Similar EIA resonance transformation to EIT one is not observed in conventional cm-size cells. A theoretical model is proposed to analyze the physical processes behind the EIA resonance sign reversal with light intensity. The model involves elastic interactions between Cs atoms as well as elastic interaction of atom micrometric-cell windows, both resulting in depolarization of excited state which can lead to the new observations. The effect of excited state depolarization is confirmed also by the fluorescence (absorption) spectra measurement in micrometric cells with different thicknesses.